(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the diverse functions of names in idiomatic expressions, focusing on how proper names—such as personal, historical, and cultural references— contribute to meaning-making in language. Names in idioms serve multiple roles including personification, historical and literary allusion, stereotype activation, metonymic reference, and stylistic enhancement. By encapsulating cultural knowledge and social values, these idioms act as linguistic shortcuts that convey complex ideas with brevity and emotional resonance. The analysis highlights both the communicative effectiveness and the potential social implications of name-based idioms, offering insights into the intersection of language, culture, and cognition.